1991
DOI: 10.3168/jds.s0022-0302(91)78492-0
|View full text |Cite
|
Sign up to set email alerts
|

Some Blood Minerals and Hormones in Cows Fed Variable Mineral Levels and Ionic Balance

Abstract: Eighty multiparous Holstein cows were assigned to eight treatments in a 2 x 2 x 2 factorial design to examine changes in serum parathyroid hormone, calcitonin, Ca, P, Mg, K, and Cl under two levels of dietary Ca and P with two anion-cation balances. Factor levels were low and high Ca (51 vs. 115 g/d), P (38 vs. 52 g/d), and cationic:anionic balance (23 vs. -8 meq). Cows were offered a TMR and an experimental mineral supplement to adjust mineral and anion-cation levels. Caudal vein blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
7
7
0
1
Order By: Relevance
“…Indeed, serum Ca and P concentration is also inversely related to parity number (Shappell et al, 1987;Romo et al, 1991) justifying the hypothesis of a lower utilization in older cows. Van de Braak and Van't Klooster (1987) argued that osteoplastic activities are less intense in older than in younger cows, which could explain a decreased responsiveness for parathyroid hormone-mediated Ca resorption and intestinal absorption in older parity cows (Romo et al, 1991). Moreover, the greater amount of milk produced by older cows during lactation could explain the lower mineral content because of the dilution.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, serum Ca and P concentration is also inversely related to parity number (Shappell et al, 1987;Romo et al, 1991) justifying the hypothesis of a lower utilization in older cows. Van de Braak and Van't Klooster (1987) argued that osteoplastic activities are less intense in older than in younger cows, which could explain a decreased responsiveness for parathyroid hormone-mediated Ca resorption and intestinal absorption in older parity cows (Romo et al, 1991). Moreover, the greater amount of milk produced by older cows during lactation could explain the lower mineral content because of the dilution.…”
Section: Discussionmentioning
confidence: 85%
“…The decrease in milk Ca and P content within increasing parity is probably due to the reduced Genetics of milk minerals and acidity utilization of these minerals in the mammary gland (Kume and Tanabe, 1993). Indeed, serum Ca and P concentration is also inversely related to parity number (Shappell et al, 1987;Romo et al, 1991) justifying the hypothesis of a lower utilization in older cows. Van de Braak and Van't Klooster (1987) argued that osteoplastic activities are less intense in older than in younger cows, which could explain a decreased responsiveness for parathyroid hormone-mediated Ca resorption and intestinal absorption in older parity cows (Romo et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are dependent on the paracellular absorption pathway to maintain the serum Ca at a steady concentration. Romo et al (1991) and Kume et al (2003) also reported that high parity in cows had a negative effect on serum Ca concentration, and serum Ca decline due to parturition in dairy cows increased with the parity. It should be considered from these reports that the action of DFA III on Ca uptake via paracellular pathway will have a relatively greater effect in multiparous cows when compared to primiparous cows.…”
Section: Discussionmentioning
confidence: 91%
“…An increase in blood calcium (Ca) ion concentrations at calving have been reported at DCAB levels of -8 mEq/kg dry matter (DM) (Phillippo Tauriainen, S. et al Effect of anionic salts on dry cows III et al 1994), -35 mEq/kg DM (Abu Damir et al 1994) or -75 mEq/kg DM (Oetzel et al 1988). However, a decrease in DCAB did not change total Ca concentration in plasma when DCAB was -8 mEq/kg DM (Phillippo et al 1994, Romo et al 1991. Although a change in total Ca concentration in plasma was noticed with -30 mEq/ kg DM in DCAB, a lack of the prophylactic effect on the occurrence of milk fever has been documented (Tucker et al 1992).…”
Section: Introductionmentioning
confidence: 98%